MODERATION EFFECT OF WORK MOTIVATION: THE EFFECT OF DIGITAL COMPETENCY ON BANK EMPLOYEE PERFORMANCE - Rei Restu Asyari; Sumardi; Nurdjanah Hamid (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This research aims to analyze the influence of digital competence on the performance of Bank Sulselbar employees both directly and using work motivation as a mediating variable. The type of this research is quantitative research with moderated analysis techniques based on the results of distributing questionnaires to 56 employees. The research results show that digital competence has a significant influence on employee performance at Bank Sulsebar. Digital skills and knowledge mastered by employees increase efficiency, productivity, and innovation capabilities in a work environment increasingly dominated by technology. This not only improves the operational effectiveness of the bank, but also helps in meeting and exceeding customer expectations in the digital age. In addition, this study also shows that work motivation plays a role as an important moderation variable in the relationship between digital competence and employee performance. Work motivation affects how effectively employees can apply their digital competencies in daily work. Motivated employees tend to be more proactive in learning new technologies, applying digital knowledge in innovative ways, and working collaboratively, which in turn improves overall performance.